Qualifications and Competencies of Guidance Teachers as Correlates with their Performance: Basis for a Proposed Enrichment Program - Recede, Reynald Alfred A.; Ignacio, Nadia C.; Paz- Muñoz, Felisa; Pekas, Monette G. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
The study aimed to determine the qualifications and competencies of guidance teachers in correlation with their performance for the school year 2018 – 2019. The status of the qualifications of the guidance teachers was determined in terms of educational attainment, level of seminars and trainings attended pertinent to guidance related work and length of service as a guidance teacher. The respondents of the study were 15 school heads, 37 guidance teachers and 1,001 teachers. The study utilized the descriptive evaluative method. Data were collected through the use of researcher – adapted questionnaire checklist. The results showed that there is no significant correlation between the qualifications of the guidance teachers and their competencies as perceived by the three groups of respondents. The results showed that there are no significant correlations between the qualifications of the guidance teachers and their performance. In consideration of the correlation that exists, the administrators and the teachers perceived that the guidance teachers’ qualifications are positively correlated with the performance. The results showed that there is a low correlation between the competencies of guidance teachers and their performance but considered to be not significant. In consideration of the administrators and teachers, the correlation is positive while for the guidance teachers themselves, the correlation is negative.